Assessment of Tissue Eosinophilia as a Prognosticator in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma—An Image Analysis Study. (19th February 2014) - Jain, Megha; Kasetty, Sowmya; Sudheendra, U. S.; Tijare, Manisha; Khan, Samar; Desai, Ami
Abstract : Association of tissue eosinophilia with oral squamous cell carcinoma has shown variable results ranging from favourable to unfavourable or even having no influence on prognosis. Also, very few studies have been done to know the role of eosinophils in premalignancy. So the present study investigated role of eosinophilic infiltration in oral precancer and cancer and its possible use as a prognosticator. 60 histopathologically proven cases (20 cases each of metastatic and nonmetastatic oral squamous cell carcinoma and oral leukoplakia with dysplasia of various grades) were included. Congo red is used as a special stain for eosinophils. Each specimen slide was viewed under high power in 10 consecutive microscopic fields for counting of eosinophils. As a result, a significant increase in eosinophil count was found in oral carcinomas compared to dysplasia. Nonmetastatic cases showed higher counts than metastatic carcinomas. So, it is concluded that eosinophilia is a favourable histopathological prognostic factor in oral cancer. Moreover, higher eosinophil counts in carcinoma group compared to dysplasia group proved that they might have a role in stromal invasion thus suggesting that quantitative assessment of tissue eosinophilia should become a part of the routine histopathological diagnosis for oral precancer and OSCC.